Fire Performance of FRCM Strengthened Columns: Experimental Investigation - Khalaf, Salem Mazen (2023)
A Master of Science thesis in Civil Engineering by Salem Mazen Khalaf entitled, “Fire Performance of FRCM Strengthened Columns: Experimental Investigation”, submitted in November 2023. Thesis advisor is Dr. Farid Abed and thesis co-advisor Dr. Ahmed El Refai. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).